1978
DOI: 10.1002/jez.1402050203
|View full text |Cite
|
Sign up to set email alerts
|

The possible influence of temporal factors in androgenic responsiveness of urogenital tissue recombinants from wild‐type and androgen‐insensitive (Tfm) Mice

Abstract: Tissue recombinants of epithelium and stroma from embryonic and neonatal urogenital rudiments derived from wild-type and feminized (Tfm/Y) mice sere grown as grafts in intact male hosts and analyzed morphologically for androgenic response. When mesenchyme of embryonic wild-type urogenital sinus (UGS) was associated with epithelium from embryonic wild-type bladder (B), the epithelium developed into glandular structures resembling prostate. In the reciprocal recombinant (B mesenchyme + UGS epithelium) the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
200
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 279 publications
(210 citation statements)
references
References 25 publications
6
200
0
2
Order By: Relevance
“…The essence of these assays is that cells are put back into their natural environment already containing the appropriate structure and supportive stroma. Because the prostate cannot easily be cleared of epithelial cells, Cunha and Lung (1978) developed a prostate tissue fragment recombination assay that has been used to study prostate development and epithelial-mesenchymal interactions. In this procedure, fragments of rodent urogenital sinus mesenchyme (UGSM) are combined with adult prostate epithelial fragments and implanted under the kidney capsule of an immunodeficient mouse to generate prostatic tubules.…”
Section: In Vivo Regeneration Assaymentioning
confidence: 99%
“…The essence of these assays is that cells are put back into their natural environment already containing the appropriate structure and supportive stroma. Because the prostate cannot easily be cleared of epithelial cells, Cunha and Lung (1978) developed a prostate tissue fragment recombination assay that has been used to study prostate development and epithelial-mesenchymal interactions. In this procedure, fragments of rodent urogenital sinus mesenchyme (UGSM) are combined with adult prostate epithelial fragments and implanted under the kidney capsule of an immunodeficient mouse to generate prostatic tubules.…”
Section: In Vivo Regeneration Assaymentioning
confidence: 99%
“…The tissue recombination procedure developed by Cunha and Lung (16) uses fragments dissected from rat or mouse urogenital sinus mesenchyme (UGSM) in combination with adult epithelial tissue to regenerate prostate-like tissues. We developed a dissociated cell system to facilitate the study of unique prostate cell subpopulations to demonstrate that a subpopulation of murine prostate cells possesses stem-like capacity for de novo tubule regeneration (17).…”
mentioning
confidence: 99%
“…Previous in vitro studies using long-term passaged cancer cell lines have demonstrated that PTEN and AKT are, respectively, negative and positive modulators of AR transcriptional activity (12-15). Some papers have reported that AKT negatively regulates AR protein levels and transcriptional activity at the posttranscriptional (16) and posttranslational (17, 18) levels.We have modified and improved a prostate cell regeneration assay in which dissociated adult murine prostate epithelial cells are combined with embryonic urogenital sinus mesenchymal (UGSM) cells and engrafted under the kidney capsule of immunodeficient host CB.17 SCID/SCID mice to regenerate murine prostate tissue (19,20). The Sca-1 surface antigen can enrich for prostatic stem cell activity, and a single stem͞progenitor cell is capable of regenerating a whole tubule containing both basal and luminal cells in such regeneration experiments (21,22).…”
mentioning
confidence: 99%
“…We have modified and improved a prostate cell regeneration assay in which dissociated adult murine prostate epithelial cells are combined with embryonic urogenital sinus mesenchymal (UGSM) cells and engrafted under the kidney capsule of immunodeficient host CB.17 SCID/SCID mice to regenerate murine prostate tissue (19,20). The Sca-1 surface antigen can enrich for prostatic stem cell activity, and a single stem͞progenitor cell is capable of regenerating a whole tubule containing both basal and luminal cells in such regeneration experiments (21,22).…”
mentioning
confidence: 99%